Crystal structure of (E)-2-(4-(1H-imidazol-1-yl)benzylidene)-7-fluoro-3,4-dihydronaphthalen-1(2H)-one, C20H15FN2O - Chen Yu; Wang Ji-Peng; Wang Mei-Dan; Yu Wen-Xiao; Cui Yao-Tian; Gao Hao-Xue; Hou Gui-Ge; Ren Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C20H15FN2O, triclinic, P 1‾ $\overline{1}$ (no. 2), a = 8.0724(1) Å, b = 9.6473(1) Å, c = 9.6635(1) Å, α = 80.903(1)°, β = 82.325(1)°, γ = 84.147(1)°, V = 733.922(14) Å3, Z = 2, Rgt (F) = 0.0366, wRref (F 2) = 0.0934, T = 293 K.